Complement-fixing antibody in human sera reactive with viral and soluble antigens of cytomegalovirus. - Cremer, N E (1975)
Antibody titers to cytomegalovirus were determined in 204 single-serum specimens and in 138 serum pairs, utilizing as antigen extracts of infected cells prepared by either freezing and thawing cells (FT antigen) or extracting them with a glycine buffer (GE antigen). With the serum pairs, 40% of the early sera and 44% of the late sera showed a fourfold or higher antibody titer with the GE antigen compared with those with the FT antigen, whereas 39% of the single sera had a fourfold or higher titer with the GE antigen. Sucrose density gradient centrifugation of the two antigen preparations indicated that the GE antigen contained two peaks of complement-fixing activity, one at a density of 1.18 to 1.22 g/cm3 and one at 1.06 to 1.10 g/cm3. The FT antigen had only one discernible peak of complement-fixing activity at 1.04 to 1.10 g/cm3. On electron microscopy, the more dense peak contained mainly nucleocapsids with some dense bodies and occasional enveloped virions, and the lighter peak was composed of amorphous material. Antibody titers obtained with the crude GE antigen and the more dense peak (designated viral antigen) were in agreement, whereas titers with the FT antigen agreed with those obtained with the lighter peak (soluble antigen). The antibody detected with both antigens was mainly immunoglobulin G.